Analysis of the influence of super high-rise building construction on large-span tunnels adjacent to overlapping tunnels. Issue 1 (January 2020) - Yu, Shun; Xiao, Bo; Zheng, Xixi
Abstract: A building site consists of a garage and two super-high-rise towers. Two-way six-lane municipal double-arch tunnel and single-tunnel double-line long-span metro tunnel overlap above and below the building site. Finite element software is used to simulate the influence of surface construction on the two tunnels. The calculation results show that the construction above the tunnel has little influence on the structural deformation of the two tunnels, and the structural displacement of the metro tunnel meets the requirements of the safety control index of the rail transit structure; because the metro tunnel bears large rock, soil and building loads above, the structural design of the metro tunnel should be strengthened to meet the bearing capacity requirements.